Sociedade cativa: entre cultura escolar e cultura prisional - uma incursão pela ciência penitenciária - Vasquez, Eliane Leal (2008)
In the present work we analyse some penitentiary rules in Brazil in the transition of the 19th to 20th century, specially, in relation to the conception of education, focusing the changing of the scholar curriculum in this period from examples of the Casa de Correção da Corte , Presídio de Fernando de Noronha and Casa de Correção da Capital Federal . Besides that, we discuss the relation between the knowledge corpus , shared by the teachers at the school of the 21st century prison, with the behaviours and knowledges corpus that the captive society produce in the prison environment through the study of case accomplished with prison-students of the Instituto de Administração Penitenciária do Amapá . So, the study object of this research correspond to an essay to construction of interface in the history of science between penitentiary science, penitentiary law and history of penal execution in Brazil